EFEKTIVITAS PELAKSANAAN METODE DRILL PADA PROSES PEMBELAJARAN AL-QUR’AN HADIS TERHADAP MINAT BELAJAR SISWA KELAS VIII DI MTS AL-IHYA TANJUNG GADING - Trisnawati, Siti (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
This research departs from the discrepancies in applying the method in learning. The author wants to know how the effectiveness of the implementation of the drill method in the learning process of Al-Qur'an Hadith on student interest in learning at MTs Al-Ihya Tanjung Gading. With this research aims to determine the effectiveness of the drill method in the process of learning Al-Qur'an Hadith with student interest in learning at MTs Al-Ihya Tanjung Gading. The background for the researcher to raise this title is because learning Al-Qur'an Hadith at MTs Al-Ihya Tanjung Gading still uses traditional learning methods, namely the lecture method, so that children feel bored and bored with these methods. Seeing this problem, the researchers were interested in taking this title and offering a drill method as this method is considered effective in improving student learning outcomes in the subject of Al-Qur'an Hadith at MTs Al-Ihya Tanjung Gading. The formulation of the problem in this study is how to implement the drill method in learning Al-Qur'an Hadith at MTs Al-Ihya Tanjung Gading. How are students' interest in learning in implementing the drill method in learning Al-Qur'an Hadith at MTs Al-Ihya Tanjung Gading. This research is a quantitative study, taking the background of MTs Al-Ihya Tanjung Gading. Data collection was carried out by conducting observations, interviews and documentation. While this data analysis technique is quantitative. Based on the research, it can be seen that the effectiveness of the implementation of the drill method is 58% on students' interest in learning, while the remaining 42% is an influence from outside this study on the motivation to learn Al-Qur'an Hadith.